Changes in cardiac autonomic regulation after prolonged maximal exercise - Hautala, A.; Tulppo, M. P.; Makikallio, T. H.; Laukkanen, R.; Nissila, S.; Huikuri, H. V. (Clinical Physiology and Functional Imaging, 2001)
Harmful cardiac events occurs frequently after exercise. However, the cardiac autonomic regulation after vigorous exercise is not well known. This study was designed to assess heart rate (HR) variability before and after a 75 km cross-country skiing race. HR variability was assessed by using standard statistical measures along with spectral and quantitative Poincare plot analysis of HR variability in 10 healthy male subjects (age 36 +/- 11 years). The average HR was at the same level 1 day after the race as before the race, but on the second day, HR was significantly lower (P<0.001) compared with the prerace and 1 day after values. The normalized high-frequency (HF) spectral component of HR variability (nuHF) was lower (P<0.01) on the first day after the maximal exercise compared with the pre-exercise values but returned to or even exceeded the prerace level on the second day (P<0.01). The changes in short-term R-R interval variability analysed from the Poincare plot were similar to those observed in the HF spectral component. The normalized low-frequency (LF) spectral component of HR variability (nuLF) was higher (P<0.01) on the first day after the exercise compared with the prerace levels and it also returned to the pre-exercise level or even dropped below it on the second day after the race. The mean time it took the HF spectral component to return to the pre-exercise level was 4.2 +/- 4.2 h (ranging from 0 to 12 h). This recovery time correlated inversely with the maximal oxygen consumption (VO2max) measured during the bicycle exercise test before the skiing race (r=-0.712, P<0.016). The cardiac vagal outflow is blunted for several hours after prolonged vigorous exercise. The recovery time of reduced vagal outflow depends on individual cardiorespiratory fitness and there is an accentuated rebound of altered autonomic regulation on the second day after prolonged exercise.